Incidencia de la contaminación orgánica y de metales pesados sobre la biodiversidad marino costera del sitio El Coco cantón Machala provincia de El Oro - Pardo Aguilar, Fausto Fernando (2012)
The province of El Oro is considered as one of the richest and most fertile mind Ecuador, with its natural resources and hydrological diversity, drawing mainly to its large production of bananas, shrimp, and gold. However, the improper exploitation of these activities over time have generated negative impacts on freshwater and marine ecosystems, due to the uncontrolled use of chemicals, antibiotics, and mining equipment in such activities, that is why the subject is presented research, "Effect of organic pollution and heavy metals on marine and coastal biodiversity of the site Machala canton coconut" for which the following aims: To determine the concentration levels of heavy metals in water, sediment and shells of Site Coco in Canton Machala, El Oro province Compare and analyze the results with the limits set for the preservation of flora and fauna. Following this research we can conclude the following: Valuation results of heavy metals, arsenic, mercury, lead and cadmium in water samples place the coconut there the presence of these metals but does not exceed the maximum permissible limits. Results of the assessment of heavy metals, arsenic, mercury, lead and cadmium in soil samples at the site the coconut there the presence of these metals but does not exceed the maximum permissible limits. Results of the assessment of heavy metals, arsenic, mercury, lead and cadmium in shellfish samples at the site the coconut there the presence of these metals that exceed maximum allowable limits.